2010
DOI: 10.1007/bf03324799
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in high-functioning persons aged 65 to 70 years: the importance of the fear factor

Abstract: In high-functioning older persons, low falls efficacy was associated with vulnerability, even after controlling for gait performance and falls history. Whether low falls efficacy is a potential target on the pathway leading to frailty should be further examined prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…Therefore, it has been suggested that poor balance confidence should rather be considered as a potential marker of frailty. For instance, in the study of well-functioning elderly subjects, those without any criteria of frailty according to Fried, but who reported some fear of falling, had similar gait performance than subjects with one or more frailty criteria but no fear [7] . In other terms, reporting some level of fear of falling was associated with a similar level of gait impairment, as observed in elderly persons already transitioning toward becoming frail.…”
Section: What Is the Epidemiological Rationale For Improving Balance mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it has been suggested that poor balance confidence should rather be considered as a potential marker of frailty. For instance, in the study of well-functioning elderly subjects, those without any criteria of frailty according to Fried, but who reported some fear of falling, had similar gait performance than subjects with one or more frailty criteria but no fear [7] . In other terms, reporting some level of fear of falling was associated with a similar level of gait impairment, as observed in elderly persons already transitioning toward becoming frail.…”
Section: What Is the Epidemiological Rationale For Improving Balance mentioning
confidence: 99%
“…Moreover, some of these studies showed that even relatively young, wellfunctioning elderly persons report some level of fear and activity restriction. For instance, in a population-based study of 860 well-functioning elderly persons aged 65-70 years, about 30% reported a concern about falling in daily activities [7,8] .…”
Section: What Is the Epidemiological Rationale For Improving Balance mentioning
confidence: 99%
See 1 more Smart Citation
“…Even among well-functioning older adults, the negative impact of concern about falling may be significant. For instance, previous work has shown that an increased level of concern about falling (assessed with Fall Efficacy Scale-International, FES-I) in robust community-dwelling older persons was associated with reduced mobility performance of similar magnitude than observed in the presence of a frailty criterion [4]. Therefore, the concern about falling and potential consecutive activity restrictions should be addressed early on to prevent these undesirable consequences [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some experts have already shown that psychological aspects predict the onset of frailty in the elderly (Ostir et al, 2004); Ostir et al (2004) showed that a high positive affect reduced the risk of the onset of frailty in a 7-year prospective study. In the anthropological approach, fear of falling, for example, can also be a frailty deficit; this variable was already found to be a determinant of health vulnerability even after controlling for falls history and gait performance among older adults (Seematter-Bagnoud et al, 2010).…”
Section: Local Evaluations For a Micro-analysis Of Frailty: The Anthrmentioning
confidence: 99%